Identification of Known and Novel microRNAs and Their Targets in Peach (Prunus persica) Fruit by High-Throughput Sequencing - Zhang, Chunhua (PLoS One, 2016)
MicroRNAs (miRNAs) are a group of non-coding RNAs that have functions in post-transcriptional gene regulation in plants. Although the most important economic component of peach trees (Prunus persica) is the fruit, not much is known about miRNAs in this organ. In this study, miRNAs and their targets were identified and characterized from libraries of small RNAs of peach fruit through Solexa based-sequencing and bioinformatics approaches. A total of 557 known peach miRNAs belonging to 34 miRNA families were identified, and some of these miRNAs were found to be highly conserved in at least four other plant species. Using the most current criteria for miRNA annotation, 275 putative novel miRNAs were predicted, and the sequencing frequencies of these novel miRNAs were less than those of the conserved miRNAs. In total, 3959 and 1614 target genes for 349 known and 193 novel miRNAs, respectively, were predicted with the criteria that a single target gene can be targeted by different miRNAs and that a single miRNA can also have a large number of target genes. Three targets were even found to be targeted by 13 novel miRNAs that contained the same complete miRNA sequence at different locations and had different scaffolds. The proteins predicted to be targeted by the miRNAs identified in this study encompass a wide range of transcription factors and are involved in many biological processes and pathways, including development, metabolism, stress responses and signal transduction. A total of 115 and 101 target genes were identified to be cleaved by 60 known miRNAs and 27 novel miRNAs through degradome sequencing, respectively. These miRNAs induce cleavage of their targets precisely at the position between nucleotides 10 and 11 of the miRNA sequences from the 5’ to the 3’ end. Thirty conserved miRNAs and 19 novel miRNAs exhibited differential expression profiles in the peach, and the expression patterns of some miRNAs appeared to be tissue- or developmental stage-specific. The findings of this study provide an important basis for the analysis of miRNAs, their targets and the functions of these targets in peach fruit.